Company Profile Website Development With 360 Interactive Product Features To Improve User Experience On Medical Devices - Muhammad Hafidz; Halimatuz Zuhriyah; Anindya A Hapsari (Jakarta Global University, 2025)
This research developed an interactive Company Profile Website for DM Medical Alkes to address the lack of digital promotion and corporate credibility. The website integrates an interactive 360° product presentation feature to enhance user experience and buyer confidence. The Agile Development method was employed, which included planning, design (UML, mockups), implementation (Next.js, Supabase), testing, and review phases. An experiment to determine the optimal number of images for the 360° feature was conducted with internal stakeholders, resulting in the use of 36 images. Comprehensive system testing was performed using Black Box Testing, which confirmed that all basic website functionalities operated optimally. User Experience (UX) Testing with the System Usability Scale (SUS) yielded an average score of 80.85 from 41 customers (categorized as